Implementasi Metode Agile pada Perancangan Sistem Informasi Wisata Desa - Ismail, Abdul Rahman; Yunus, Yulanda; Senung, Bahtiar; Pratama, A Mulawati M (Journal of Information System Research (JOSH), 2024)
Information and Communication Technology (ICT) has become a trend in all aspects of life, following the flow of contemporary information technology development, from business practitioners to government sectors. If the tourism sector is well-managed and developed, it can significantly contribute to the nation's financial resources. However, until now, tourist attractions, including natural, cultural, and historical sites in Biluhu Timur Village, have not been well-publicized. As a result, the available tourism information is not well-known to the broader public and tourists. The purpose of this research is to design a web-based tourism information system that facilitates tourists and the community in accessing tourism information in Biluhu Timur Village, Batudaa Pantai District. The method used is Agile. The system is designed using PHP and HTML programming languages, with MySQL as the database. For modeling, Unified Modeling Language (UML) is used. The system testing, performed using black-box testing, yielded results that met the expectations.